Mindfulness Based Stress Reduction (MBSR) Menurunkan Tingkat Stres Sindrom Pramenstruasi Remaja - Kharisma Dwi Anggraini; Sri Sumarni; Sri Endang Windiarti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Premenstrual syndrome (PMS) is a symptom of physical and psychological discomfort before menstruation. One of the causes of premenstrual syndrome is stress. Prevention to reduce premenstrual syndrome is Mindfulness Based Stress Reduction (MBSR). Mindfulness Based Stress Reduction (MBSR) is a self-regulation approach that is also used to reduce stress and manage emotions by increasing awareness of what is felt both physically and psychologically without judging it.  To determine the effect of mindfulness-based stress reduction on stress levels in adolescents with premenstrual syndrome. This research is a true experiment with a pretest-posttest control group design. The intervention group sample was 18 people and the control group sample was 18 people. The result of the study is that MBSR consisting of 8 sessions with 2 meetings per week had an effect on reducing stress level (p value = 0.001) with an effect size strength of 1,251 which means a large category. Administering mindfulness-based stress reduction therapy to adolescents with premenstrual syndrome has been proven to reduce stress levels with a large category of effect size strength. Keywords: MBSR, Stress, Premenstrual Syndrome.  ABSTRAK Premenstrual syndrome (PMS) adalah gejala ketidaknyamanan pada fisik maupun psikologis sebelum menstruasi. Salah satu penyebab sindrom pramenstruasi adalah stress. Pencegahan untuk mengurangi sindrom pramenstruasi adalah Mindfulness Based Stress Reduction (MBSR). Mindfulness Based Stress Reduction (MBSR) adalah pendekatan pengaturan diri yang juga digunakan untuk mengurangi stress dan mengelola emosi dengan meningkatkan kesadaran atas apa yang dirasakan baik fisik maupun psikis tanpa menghakiminya.  Menganalisis mindfulness-based stress reduction terhadap tingkat stress pada remaja dengan sindrom pramenstruasi. Penelitian ini adalah true experiment dengan pendekatan pretest-posttest kontrol group design. Jumlah sampel kelompok intervensi 18 orang dan jumlah sampel kelompok kontrol 18 orang. Hasil penelitian pemberian MBSR yang terdiri dari 8 sesi dengan 2 kali pertemuan dalam seminggu berpengaruh pada penurunan skor tingkat stress (p value = 0,001) dengan kekuatan effect size 1,251 yang berarti kategori besar. Pemberian terapi mindfulness based stress reduction pada remaja dengan sindrom pramenstruasi terbukti dapat menurunkan skor tingkat stress dengan kekuatan effect size kategori besar. Kata Kunci: MBSR, Stress, Sindrom Pramenstruasi.